Perceptual filling-in of stereoscopically presented targets - Couto, Márcia Furukawa (2007)
PURPOSE: To investigate the influence of parametric variation on the filling-in latency of stereoscopically presented stimuli. METHODS: Anaglyphs were created using two circular patches of 0.3º diameter, 0.5º disparity and 6º eccentricity from fixation point. Targets were presented at the visual field midline, 90º and 270º positions, with crossed and uncrossed disparity. The time elapsed for disappearance of the target under voluntary steady fixation was computed. Eighteen subjects tested. RESULTS: There was no significant difference between crossed and uncrossed disparities, nor between near or far from the vertical horopter line. The significant difference was between upper and lower visual field positions. CONCLUSION: The results show that: (i) stereoscopic presentation does not influence the target filling-in latency; (ii) differences between dorsal and ventral visual stream might influence target filling-in latency.